Civil position in the research of professor I. I. Gorelik - Rybaklyucheva, Olga Z. (Journal of the Belarusian State University. Law, 2022)
The scientific work of professor I. I. Gorelik in the organisation of work with volunteer squads, his active civic position, the views of the scientist on the participation of citizens in the protection of public order and their training are studied. It is noted that the views and approaches of the scientist have not lost their relevance today, in connection with it the necessity of recognising volunteer squads as an object of personnel policy and a priority source of forming the personnel potential of internal affairs bodies is substantiated.
Keywords: voluntary squad; I. I. Gorelik; personnel policy in the internal affairs bodies; public order; personnel policy objects; members of the voluntary squad